2020
DOI: 10.3389/fnagi.2020.00250
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Relationship Between Cognitive Flexibility and White Matter Integrity in Individuals at Risk of Parkinson’s Disease

Abstract: Background and Objective: Executive dysfunction is the most common cognitive impairment in Parkinson's disease (PD), occurring even in its early stages. In our study, we applied diffusion tensor imaging (DTI) to investigate white matter integrity and its association with a specific executive function such as cognitive flexibility in individuals with risk factors for PD. Methods: We examined 50 individuals with risk factors for developing PD and 24 healthy controls from the TREND (Tübinger Evaluation of Risk Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The Research Domain Criteria (RDoC) approach emphasizes that flexibility dimensions can extend beyond traditional diagnostic categories, urging the integration of diverse data levels, spanning genomics, neural circuits, and behavior, including self-report measures such as participant-filled questionnaires. Cognitive and emotional rigidity or inflexibility represents commonly observed characteristics across various mental illnesses, particularly in clinical conditions manifesting early in life, such as Parkinson’s Disease (PD) and Anorexia Nervosa (AN), depression and bipolarism ( Pantelis and Andrewes, 1995 ; Cools et al, 2001 ; Díaz-Santos et al, 2015 ; Pietschnig et al, 2016 ; Alzaid et al, 2020 ). Recent research has identified a correlation between motor stiffness in PD and executive processes (attention shifting and conflict monitoring), processes known to be influenced by cognitive procedural rigidity ( Cools et al, 2001 ; Díaz-Santos et al, 2015 ; Alzaid et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Research Domain Criteria (RDoC) approach emphasizes that flexibility dimensions can extend beyond traditional diagnostic categories, urging the integration of diverse data levels, spanning genomics, neural circuits, and behavior, including self-report measures such as participant-filled questionnaires. Cognitive and emotional rigidity or inflexibility represents commonly observed characteristics across various mental illnesses, particularly in clinical conditions manifesting early in life, such as Parkinson’s Disease (PD) and Anorexia Nervosa (AN), depression and bipolarism ( Pantelis and Andrewes, 1995 ; Cools et al, 2001 ; Díaz-Santos et al, 2015 ; Pietschnig et al, 2016 ; Alzaid et al, 2020 ). Recent research has identified a correlation between motor stiffness in PD and executive processes (attention shifting and conflict monitoring), processes known to be influenced by cognitive procedural rigidity ( Cools et al, 2001 ; Díaz-Santos et al, 2015 ; Alzaid et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive and emotional rigidity or inflexibility represents commonly observed characteristics across various mental illnesses, particularly in clinical conditions manifesting early in life, such as Parkinson’s Disease (PD) and Anorexia Nervosa (AN), depression and bipolarism ( Pantelis and Andrewes, 1995 ; Cools et al, 2001 ; Díaz-Santos et al, 2015 ; Pietschnig et al, 2016 ; Alzaid et al, 2020 ). Recent research has identified a correlation between motor stiffness in PD and executive processes (attention shifting and conflict monitoring), processes known to be influenced by cognitive procedural rigidity ( Cools et al, 2001 ; Díaz-Santos et al, 2015 ; Alzaid et al, 2020 ). Conversely, AN is marked by emotional rigidity and challenges in transitioning between cognitive or affective states ( Friederich and Herzog, 2011 ; Abbate-Daga et al, 2014 ; Halls et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The white matter requires a steady supply of blood through small blood vessels to maintain normal physiological functions ( 2 ). Cerebrovascular disease can cause a reduction or interruption of blood flow to these vessels, leading to the development of white matter hyperintensities that can be diagnosed through MRI image ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive and emotional rigidity or inflexibility are commonly observed characteristics of many mental illnesses [3,16,[30][31][32][33][34][35], specifically in clinical conditions that manifest in early life, such as Parkinson Disease (PD) and Anorexia Nervosa (AN). These traits have been extensively documented in the literature with numerous studies specifically examining their presence in PD [30,31,33,36,37] and AN [38][39][40].…”
Section: Introductionmentioning
confidence: 99%